A versatile high resolution scanning tunneling potentiometry implementation - Druga, Thomas; Wenderoth, Martin; Homoth, Jan; Schneider, M. Alexander; Ulbrich, Rainer G. (Review of Scientific Instruments, 2010)
We have developed a new scanning tunneling potentiometry technique which can-with only minor changes of the electronic setup-be easily added to any standard scanning tunneling microscope (STM). This extension can be combined with common STM techniques such as constant current imaging or scanning tunneling spectroscopy. It is capable of performing measurements of the electrochemical potential with microvolt resolution. Two examples demonstrate the versatile application. First of all, we have determined local variations of the electrochemical potential due to charge transport of biased samples down to angstrom length scales. Second, with tip and sample at different temperatures we investigated the locally varying thermovoltage occurring at the tunneling junction. Aside from its use in determining the chemical identity of substances at the sample surface our method provides a controlled way to eliminate the influence of laterally varying thermovoltages on low-bias constant current topographies. (C) 2010 American Institute of Physics. [doi:10.1063/1.3469809]